I love Lucy. The final season: 7, 8 & 9 [videorecording (DVD)] - Ball, Lucille, 1911-1989; Arnaz, Desi, 1917-1986; Frawley, William, 1887-1966; Vance, Vivian; Keith, Richard, 1950- (CBS Broadcasting Inc., 2015)
Following its wildly successful six-season run, "I love Lucy" expanded to a one-hour format as "The Lucille Ball-Desi Arnaz show" (later released as "The Lucy-Desi comedy hour"). These hilarious specials debuted with the 75-minute-long "Lucy takes a cruise to Havana" in which Lucy McGillicuddy--vacationing with her best friend Susie MacNamara--meets Ricky Ricardo for the first time. In a subsequent show, Lucy attempts to get chummy with new neighbor Tallulah Bankhead, with predictably wacky results. Then, when Little Ricky's dream of having a horse seems to be just that--a dream--Lucy finds a way to win one for him. From shenanigans in a men-only Geisha house in Tokyo to clowning with famed performer Red Skelton in Alaska and bullfighting in Mexico, Lucy and Desi's star-studded TV episodes continue the love, laughs and classically funny situations that make "I love Lucy" one of television's greatest comedy series.